Karakter Qur'ani pada Animasi One Piece Arc Arabasta - Isman Ahadi Lebu Raya; Muhammad Fattah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
There are various characters that can be drawn from the One Piece animation that need to be studied and explored further so that the large number of fans can emulate the relevance of Quranic characters in their favorite animation. This research stems from the phenomenon of discovering the representation of character relevance to the teachings of the Qur'an in an animation called One Piece, focusing on the research to determine how the Quranic character traits are depicted in the One Piece Arabasta Arc, and how the visualizations of these Quranic characters are presented in the One Piece Arabasta Arc. This research uses a qualitative approach. The research results illustrate that there are 18 findings in episodes 97, 99, 103, and 108 that indicate values in line with the character traits or moral teachings of the Qur'an. In episode 97, there are 4 character values: stop complaining, avoid greed and wastefulness, don't lie, and help others. In episode 99, there are 6 character values: love for the homeland, helping others, fighting for a cause, feeding the hungry, and consulting others. Meanwhile, in episode 103, there are 4 character values: obedience, fighting for a cause, friendliness, and avoiding bad assumptions. Additionally, in episode 108, there are 4 character values: helping others, fighting for a cause, and avoiding bad assumptions. Furthermore, the visualization of Quranic characters in the One Piece animation can be seen through the elements of film production, using narrative elements by observing the characters and the message of the story.